A Study On The Ambiguity Found In English Exercises Of Vocational School Student's Exercise Books - Pramitasih, Atik (2012)
The study aims on identifying the types, describing the frequency and the dominant type and also describing the causes and ways to disambiguate 101 ambiguous sentences found in vocational school student's exercise books entitled Forum, Pista, Prestige 1, Prestige 2, Prestige 3, Prestige 4, Modul Mentari 1 and Modul Mentari 2. The object of the study is the ambiguous word or sentence in those exercise books. The type of this study is qualitative research. The method of collecting data is documentation. The technique of the data analysis is using descriptive qualitative. It means the researcher identifying the types of ambiguity by Hurford Heasly and James theory for lexical ambiguity and Kreidler theory for syntactical ambiguity, describing the frequency of each ambiguity by using table and chart, deciding the most dominant ambiguity and then describing the causes and the ways to disambiguate the ambiguous sentences by using different ways from some linguists. The finding shows that the writer finds lexical ambiguity (23,8%) and structural or syntactic ambiguity (76,2%). Lexical ambiguity divided into some part of speech; verbs (3%), nouns (16,8%), and adjectives (4%). Syntactic ambiguity divided into surface-structure ambiguity (58,4%); a coordinate head with one modifier (8,91%), a complement and modifier or two complements (23,8%), a head with an inner modifier and an outer modifier (24,7%), certain function words, including not, have possible differences in scope (1%) and deep-structure ambiguity (17,8%); gerund+object or participle modifying a noun (2%), and also certain noun phrase (15,8%). The dominant type of ambiguity is 77 sentences (76,2%) of structural ambiguity. The writer finds 1) without context, 2) ambiguous word order, and 3) improper or missing punctuation, and 4) faulty of sentence structure as the reasons of ambiguity that can be resolved by using paraphrasing, adding preposition of, moving sentence construction, adding additional context, hyphen (-) and picture.